Analisis Ekspor dan Produktivitas Tenaga Kerja di Industri Minyak Kelapa Sawit Indonesia: Bukti Empiris di Level Perusahaan Menengah-Besar Tahun 2010-2015 - Allyssa Noor Rahmadhania (Universitas Diponegoro, 2021)
This study aims to estimate the effect of exports on labor productivity in the Indonesian palm oil industry for the 2010-2015 period. This study uses two models. In Model I, export is represented by a dummy variable, while in Model II it is represented by a percentage of the value of exported production. The estimation method used in this study is a panel with a random effect model (REM) method. The results showed that capital, wages and market share had a positive effect on labor productivity. The increase in this variable will increase productivity. Conversely, firm size has a negative effect on labor productivity. Indicates that medium-sized companies have higher productivity than large companies. Meanwhile, export variables both dummy and export percentage are not significant. It shows that there is no difference in labor productivity between companies that export and not.